Le campagne lombarde, tessera chiave del mosaico agrario europeo (Glocalism: Journal of Culture, Politics and Innovation, 2014)
A comprehensive historiography of the agricultural development in continental Europe, from the medieval period until the XX century, does not exist. Indisputably, modern agriculture is essentially an outgrowth of the humid temperate regions bordering the English Channel, but English, French and German scholars were wrong to identify these regions as the only cradle of the modern agricultural revolution.The historiography of agronomic technologies can easily underscore the importance of the Po Valley in this process because of the leading role of water in the development of a more sophisticated agriculture. In fact, drawing a connection between the grain and forage farming, which had renewed Flemish and English agriculture (but also being blessed with a warmer climate capable of exploiting the potential of the first capillary irrigation system), in the successive decades of the first Millennium, Lombard agriculture realized an amount of production that was unimaginable in Flanders, Picardy, Normandy, Holstein and Jutland, thanks to the connection between grain farming and dairy production. After having reached exceptional levels of productivity as well as predating the agricultures of the same historical period, the agriculture of the Po Valley region settled into a premature twilight.In fact, whilst a more scientific agriculture was being born in England and France, the Italian countryside returned to a past situation with medieval characteristics. Only in XVIII century, in the Lombard countryside it was rediscovered, under the Austrian-Hungarian domination, the old prosperity founded, above all, upon traditional methods. These traditional ways were most distant from the scientific applications that were assuming the role of the “engine of progress” in other European cultivations. The agriculture of Lombardy joined this “engine of progress” only after the mid XIX century.
Keywords: agricultural revolution; agronomic technologies; Lombard agriculture; irrigation system; Po Valley